The results and comparison of rubber band ligation and injection sclerotherapy supplemented by high-fibre diet in the treatment of second-degree internal hemorrihoids - , Ahmet GÖRGÜL, B. Bülent MENTEŞ, Öge TAŞÇILAR, Yüksel ATEŞ, Uğur KANDİLCİ, Ertan TATLICIOĞLU (Turkish Journal of Gastroenterology 1, 2019)
-